2014
DOI: 10.2174/138920101512141202111915
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Iron Homeostasis and Therapeutic Implications of Iron Chelators in Cancer

Abstract: Iron metabolism and homeostasis are imperative for the maintenance of normal physiological activities due to the element's critical involvement in a wide variety of crucial biological processes like cellular respiration, metabolic pathways, DNA replication, repair, detoxification, neurotransmission and cellular signaling. Being a key contributor of crucial machineries regulating cellular proliferation and survival, it facilitates the process of tumor growth and development. Thus, tumor cells strive to acquire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…These compounds have been used clinically to treat iron-overload conditions ( e.g. haemochromatosis, thalassemia [53] ) and, by limiting iron availability for DNA synthesis, may also be effective anti-neoplastic agents that suppress growth and hyperproliferation of cancer cells [54] . However, our data would indicate that, unless iron chelators are used at concentrations that maintain iron stores within tight physiological limits or offer selective toxicity towards cancer cells, they may also inadvertently compromise function of normal cells through their effect not just on the mTOR pathway, but upon expression/activity of other proteins with key roles in signalling, metabolism and cell cycle biology.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have been used clinically to treat iron-overload conditions ( e.g. haemochromatosis, thalassemia [53] ) and, by limiting iron availability for DNA synthesis, may also be effective anti-neoplastic agents that suppress growth and hyperproliferation of cancer cells [54] . However, our data would indicate that, unless iron chelators are used at concentrations that maintain iron stores within tight physiological limits or offer selective toxicity towards cancer cells, they may also inadvertently compromise function of normal cells through their effect not just on the mTOR pathway, but upon expression/activity of other proteins with key roles in signalling, metabolism and cell cycle biology.…”
Section: Discussionmentioning
confidence: 99%
“…However, many clinical trials have failed to show any benefits of the use of these chelators in these diseases [ 146 ]. Compared to the efficacy of iron chelators for cancer, some clinical evidence shows that iron chelators also have obvious toxic side effects [ 147 , 148 ]. A recent review also showed concerns about clinical efficacy and side effects of iron chelators for iron storage diseases [ 149 ].…”
Section: Therapeutic Opportunities For Cancer Based On Altered Iromentioning
confidence: 99%
“…Moreover, these targets could be used for the development of new diagnostic tools able to provide an insight into the frequency of CSC within the tumor. Based on evidences obtained from both epidemiological and molecular studies, new insights are emerging linking the presence of excess iron and altered iron metabolism to cancer [14, 15]. Recently, Schonberg et al [16] have demonstrated an enhanced iron scavenging ability in CSC of glioblastoma multiforme, due to a significant overexpression of the transferrin receptor (TfR) and a consequent increase in transferrin uptake, which is indicative of increased tumorigenicity.…”
Section: Introductionmentioning
confidence: 99%